Moms' behavior towards the children's Febrile Seizure - Kasmawati, Kasmawati (Sean Institute, 2022)
Febrile Seizure are one of the most common health issues experienced by children; if not promptly handled correctly, they can pose fatal risks leading to death. The main objective of this study is to try to obtain an overview of maternal behavior in managing fever convulsions in children. A literature review method was utilized for this study. Data was systematically gathered from journals and scientific databases and processed accordingly. The review's findings indicate several crucial points. Firstly, maternal knowledge regarding the management of fever convulsions is still relatively low, necessitating improvement, either through education or independently by the mothers. Secondly, there is a strong correlation between the mother's level of knowledge and her ability to manage a child experiencing fever convulsions. Studies reviewed found that the level of skill possessed by the mother significantly determines her capability to handle febrile seizure experienced by the child.